Fostering a community of PHAROS scholars through the adoption of open standards. (January 2020) - Delmas-Glass, Emmanuelle; Sanderson, Robert
Abstract : The PHAROS consortium is adopting the Linked Art data model to make its descriptions of photo archives collections available as Linked Open Data to further support scholars in their research. Linked Art is both a community and a data model. As an international community, it works together to create a shared data model to describe art. As a data model, it is a data profile of the CIDOC Conceptual Reference Model and using Linked Open Data techniques. The goal of Linked Art is to enable museums and developers to engage in LOD initiatives more easily by providing them with shared data modelling decisions and consistent design principles.